2017
DOI: 10.1111/pace.13195
|View full text |Cite
|
Sign up to set email alerts
|

Off the pedal: Fluoroless transseptal puncture in pediatric supraventricular tachycardia ablation

Abstract: Fluoroless TS procedures utilizing ICE can safely be performed in pediatric patients without adding substantial procedural times compared with those utilizing fluoroscopic guidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Three-dimensional EAM has been used in association with catheter ablation for atrioventricular nodal reentrant tachycardia, cavotricuspid isthmus-dependent atrial flutter, and premature ventricular contraction, especially in pediatric and pregnant patients. [12][13][14][15][16][17] Three-dimensional EAM holds promise as a tool for use in combination with transseptal puncture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three-dimensional EAM has been used in association with catheter ablation for atrioventricular nodal reentrant tachycardia, cavotricuspid isthmus-dependent atrial flutter, and premature ventricular contraction, especially in pediatric and pregnant patients. [12][13][14][15][16][17] Three-dimensional EAM holds promise as a tool for use in combination with transseptal puncture.…”
Section: Discussionmentioning
confidence: 99%
“…Clark et al reported a cohort study in which EAM was used in combination with ICE to perform transseptal puncture. By pulling down the ablation catheter, the authors located the position of the foramen ovale 17 . However, the advantages of EAM were not fully utilized in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as the volume of atrial fibrillation procedures rises, concern over patient and staff radiation exposure continues to increase 2, 12, 13. While nonfluoroscopic guidance systems, such as ICE, TEE, and 3D EAM, have been increasingly used in catheter ablation procedures to reduce or completely eliminate fluoroscopy,4, 5, 6, 7, 8, 14 transseptal access is often regarded as the main challenge in completely nonfluoroscopic catheter ablation 15 . This step requires visualization of the drop-down of the device tip from the brachiocephalic vein or SVC to the fossa ovalis, which is traditionally performed under fluoroscopic guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric electrophysiology has been at the forefront of zerofluoroscopic techniques over the past decade [39][40][41]. Given the young age of these patients and their relatively long life expectancy compared with adults, providers must carefully weigh the effects of ionizing radiation exposure.…”
Section: Unique Populationsmentioning
confidence: 99%